The relationship between health and political ideology begins in childhood - Viji Diane Kannan; Julianna Pacheco; Kelly Peters; Susan Lapham; Benjamin P. Chapman (SSM: Population Health, 2022)
We investigate whether childhood health status influences adult political ideology and whether health at subsequent life-stages, adolescent personality traits, or adolescent academic aptitude mediate this relationship. Using a national longitudinal cohort sample, we found that better health among children under age 10 was positively related to conservative political ideology among adults over age 64. Children with excellent health compared to very poor health were 16 percentage points more likely to report having a conservative political ideology in adulthood. Children with excellent health compared to very poor health were 13 percentage points less likely to report having a liberal political ideology in adulthood. Adults who had excellent health as children were 30 percentage points more likely to report conservative ideology than liberal ideology. However, the difference in ideological position for adults who had very poor childhood health was negligible. That is, the health and ideology relationship is being driven by those who were healthier early in life, after controlling for family income and material wealth. No evidence was found for mediation by adolescent heath, adult heath, adolescent personality traits, or adolescent academic aptitude. The magnitude of the coefficient for childhood health was substantively and statistically equivalent across race and sex. We discuss the possibility that, instead of being mediated, childhood health may actually be a mediator bridging social, environmental, and policy contexts with political ideology. We also discuss the potential of social policy to influence health, which influences ideology (and voting participation), which eventually circles back to influence social policy. It is important to understand the nexus of political life and population health since disparities in voice and power can exacerbate health disparities.